Role of Immunohistochemistry in the Diagnosis of Solitary Fibrous Tumor, a Review - Bita Geramizadeh; Mahsa Marzban; Andrew Churg (Iranian Society of Pathology, 2016)
Background: Solitary fibrous tumor (SFT) is a mesenchymal tumor which is most commonly seen in the pleura; however it can be seen in other organs such as the meninge, gastrointestinal tract, soft tissue, bone, and skin. SFT should be differentiated from other mesenchymal tumors in these organs. Immunohistochemistry plays a pivotal role for the histopathologic diagnosis of this tumor. Currently, new markers have been introduced which has been very useful for definite diagnosis of SFT along with other markers in each specific location which are negative in SFT. Methods: Here we review the reported positive and negative immunohistochemical markers of SFT in the English literature with the emphasis on the useful markers in each specific organ. We explored the English literature from 1990 through 2015 via PubMed, Google, and Google scholar using the following search keywords: Solitary fibrous tumor, Solitary fibrous tumor and immunohistochemistry, Solitary fibrous tumor and diagnosis, Solitary fibrous tumor and histogenesis, Solitary fibrous tumor and prognosis, Solitary fibrous tumor and hemangiopericytoma, Solitary fibrous tumor and differential diagnosis, Solitary fibrous tumor and markers. Results: The most important and valuable positive markers in SFT are CD34, CD99, Bcl-2 and STAT-6.There are consistently negative markers in this tumor as well, used according to the tumor location, such as EMA and S100 Conclusion: Immunohistochemistry is very useful for the diagnosis of solitary fibrous tumor and for its differentiation with other spindle cell mesenchymal tumor in different locations.   How to cite this article: Geramizadeh B, Marzban M, Churg A.  Role of Immunohistochemistry in the Diagnosis of Solitary Fibrous Tumor, a Review. Iran J Pathol. 2016; 11(3):195-293.